The influence of various levels of supplemental starch and degradable intake protein on prairie hay intake and digestion by beef steers - Cochran, R.C.; Vanzant, E.S.; Titgemeyer, Evan C.; Jones, Timothy J.; Olson, K. C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to determine the effect of varying the amount of supplemental degradable intake protein (DIP) and starch on prairie hay intake and digestibility. In general, DIP increased forage intake, whereas starch decreased intake. Diet digestibility also improved with increasing DIP; however, the effect of starch on digestion depended on the level of feeding. Digestible dry matter intake (which estimates total energy input) responded dramatically to DIP but not to starch. These results illustrate the positive effect of DIP on forage intake and digestibility; however, supplying additional starch within a DIP level appeared to have minimal effect on altering total energy supply.
Keywords: Beef; Steer; Protein and starch supplementation; Intake